LOCUÇÕES EM TEXTOS DE ESTUDANTES DO ENSINO MÉDIO: UM OLHAR FRASEOLÓGICO - Katiane Coelho Vieira Schleich (2024)
Phraseology is a subject of linguistics that studies the phraseological unities, which, according to Corpas Pastor (1996), are expressions formed by multiple words, are institutionalized, are stable in several ways, present certain syntactic or semantic particularities, and are able to get modifications in its own elements. The theoretical contribution of this research is based on the studies of Casares Sanchez (1950), Zuluaga (1980) and specially of the Spanish linguist Glória Corpas Pastor (1996). According to the linguist, the phraseological units are divided into colocations, locutions, and phraseological statements. The main goal of this research is to build a corpus of phraseological units using high school students' essays as sources. The specific goals are: i) conduct a survey of phraseological units in argumentative and narrative texts; ii) examine prepositional and conjunctive phrases in high school students' essays, based on the assumptions of Corpas Pastor; iii) observe the frequency of connective phrases in texts written by high school students. The corpus of this research is made of essays that were produced by high school students from a public school in Campo Grande-MS. There were made about one hundred and ninety essays, divided into the mentioned genres. It was necessary the use of the software of lexical analysis AntConc to extract the phraseological unities. The teaching of a mother language has the goal to develop discursive capacity, so they can make and capture texts in their different modalities (MONTEIRO-PLANTIN,2014). For that, reflection on the language's work in the learning context is necessary. The work with different textual genres on the high school's phases, the study of connective phrases, as well the conjunctions, are relevant because they characterize as important elements of sequential cohesion. This factor of textuality along with coherence is available in the entrance exams. We could conclude that most prepositional and conjunctive phrases were used with meanings consistent with dictionaries, such as "de acordo com" (according to), "além de" (besides), and "para que" (so that). We observed improper use of a few connective phrases, like the phrase "perto de" (near). There were variations in the use of some phrases, such as "não só... mas também" (not only... but also).